Description of a new species of deep-sea spider crab from the genus Crocydocinus Lee, Richer de Forges & Ng, 2019, from the south-eastern Arabian Sea (Crustacea: Decapoda: Majoidea: Epialtidae) - Padate, Vinay P.; Lee, Bee Yan; Cubelio, Sherine Sonia (Zootaxa, 2020)
A new species of spider crab is described from two male specimens collected from the southeastern Arabian Sea. This species differs from its congeners in the absence of uograstric granule on carapace, the presence of two granules along lateral margin of carapace at branchial region, the presence of granules on P2–P4 dactyli and the constricted distal tip of the male first gonopod.